Occurrence and significance of cystoliths in Acanthaceae - D.A.Patil2, Patil A.M.1 and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-ansi-language: EN-US; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The present authors studied foliar anatomical features of 43 species belonging to 22 genera of the family Acanthaceae. Cystoliths are characteristic of the family. However, they are totally absent in Acanthus spinosus L., Adhatoda beddomei C.B.Clarke and Staurogyne zeylanica (Nees) O. Ktze. Generally, they are present in laminar epidermis, petiolar epidermis and ground tissue. They exhibit different shapes, sizes and even colors. In some taxa, both ends of cystoliths are obtuse or acute, whereas in others one of the ends of cystolith are either obtuse or acute. They observed either single or double. This communication reviewed their occurrence in the family and highlighted their taxonomic significance.